Chunky graphite in spheroidal graphite iron: review of recent results and definition of an predicting index. (May 2019) - Sertucha, Jon; Lacaze, Jacques; González-Martínez, Rodolfo
Abstract: Graphite degeneracy in heavy-section spheroidal graphite cast irons is mostly associated with the formation of chunky graphite which consists of large eutectic cells with interconnected graphite strings. At low level, appearance of chunky graphite is limited to its non-aesthetic effect on machined surfaces, while at higher level it is detrimental for mechanical properties of the components. Chunky graphite is often related to high silicon levels and too high cerium additions during the spheroidization treatment. The appearance of this defect may be limited by controlled additions of antimony that is thought to tight the excess of cerium, but other impurities and low level elements may have to be considered during melt preparation. This contribution proposes a review of recent results and approaches on chunky graphite appearance, primarily but not exclusively in the case of heavy-section cast irons. Based on this literature review and series of experimental data, a predictive index for evaluating the risk of chunky graphite appearance is proposed. Lines for further research work aimed at a better understanding of graphite degeneracy are finally suggested.